Modeling hydrogel-controlled micro-reactors for enzyme assays with finite elements for improved flow and filling distribution - Mehner, Philipp J.; Obst, Franziska; Simon, David; Tang, Jing; Beck, Anthony; Gruner, Denise; Busek, Mathias; Appelhans, Dietmar; Marschner, Uwe; Voit, Brigitte; Richter, Andreas (ASME 2018 Conference on Smart Materials, Adaptive Structures and Intelligent Systems, SMASIS 2018, 2018)
We propose an improved micro reactor design for a scalable microfluidic device, in which enzymes are immobilized in a hydrogel matrix. Furthermore, fluid flow is controlled by means of hydrogel-based micro-valves. In this work, computational flow simulations will be compared to experimental results to highlight new design ideas and to improve wetting and concentration distribution through the entire chamber volume, even for high aspect ratios. Additionally, modelling concepts will be introduced to efficiently describe multi-domain problems like enzyme reactions. With the help of a computer-aided design process which is capable to simulate hydrogel-based microfluidic systems it is possible to better understand, predict and visualize the behavior of micro-reactors and support the development of highly integrated hydrogel-based microfluidic circuits.
CRIS-Team Scopus Importer:2022-04-14